2018
DOI: 10.26452/ijrps.v9i3.1630
|View full text |Cite
|
Sign up to set email alerts
|

Metformin compared to insulin for the management of gestational diabetic

Abstract: A prospective comparative two arms study done in Al Kadhimiya teaching hospital for 1 year duration from June 2017 till June 2017, this study included 150 women with singleton pregnancies diagnosed with gestational DM. The primary endpoints were neonatal outcomes which include; neonatal hypoglycemia (≥2 neonatal glucose values 46.8 m/dL), respiratory distress (admission to neonatal care unite NUC), need for phototherapy (neonatal jaundice), 5-minute Apgar scores below 7, or premature birth (<37 weeks of ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There were 34 eligible studies conducted from year 2000 till 2019; 11 studies which compared glyburide and insulin,[ 12 13 16 18 19 21 23 27 30 31 32 ] 18 compared metformin with insulin[ 7 8 9 14 15 20 24 25 26 33 34 35 36 37 38 39 40 41 ] and 5 assessed the efficacy of metformin with glyburide[ 6 18 22 28 29 ] [ Table 1 ] including a total of 6935 pregnant women having GDM.…”
Section: Resultsmentioning
confidence: 99%
“…There were 34 eligible studies conducted from year 2000 till 2019; 11 studies which compared glyburide and insulin,[ 12 13 16 18 19 21 23 27 30 31 32 ] 18 compared metformin with insulin[ 7 8 9 14 15 20 24 25 26 33 34 35 36 37 38 39 40 41 ] and 5 assessed the efficacy of metformin with glyburide[ 6 18 22 28 29 ] [ Table 1 ] including a total of 6935 pregnant women having GDM.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in the literature examined the currently investigated markers to varying degrees. [31–36] In Kassahun et al study in Ethiopia, a cross-sectional study that examined 136 pregnant women (46 with PE), all women were in their third trimester, and NLR showed poor ability to differentiate between PE and control (AUC = 0.609); however, NLR was the best parameter in the study according to receiver operator curve analysis. [37] NLR serves as an indicator of both systemic inflammation and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 14 15 16 ] More recent studies also found that metformin was not associated with any maternal or fetal complications, except for a slight increase in the risk of preterm birth. [ 8 17 18 19 20 21 22 ] Recent meta-analysis studies also reported on the benefits of metformin on fetal outcomes, including lowered risk of neonatal hypoglycemia, large for gestational age babies, and shorter neonatal intensive care unit stay. [ 5 6 7 23 ]…”
Section: Discussionmentioning
confidence: 99%